Athletic performance, sports experience, and exercise addiction: an association study on ANKK1 gene polymorphism rs1800497 - Bayraktar, Isık; Cepicka, Ladislav; Barasinska, Magdalena; Kazan, Hasan Huseyin; Zorba, Erdal; Ergun, Mehmet Ali; Eken, Özgür; Ceylan, Halil İbrahim; Bulgay, Celal; Gabrys, Tomasz (Frontiers in Psychology, 2023)
Exercise addiction is a phenomenon being able to affecting the athletic performance. The gene, ANKK1 and the polymorphism NM_178510.2:c.2137G>A (rs1800497) has been linked to the exercise addiction. However, further studies on diverse populations and sport branches are needed to totally explore the possible association of this polymorphism with the athletic performance. Thus, the present study aims to decipher any possible relations of the rs1800497 polymorphism with the athletic performance/personal best (PB) and sport experience of elite athletes. Sixty volunteer elite athletes (31 sprint/power and 29 endurance) and 20 control/sedentary participated in the study. The polymorphism was genotyped using whole exome sequencing approach and PB were determined according to the International Association of Athletics Federations (IAAF) score. Our results underlined that there were not any significance differences for both allele and genotype frequencies between the groups in terms of athletic performance, although the frequency of allele G was higher (p>0.05). Nevertheless, sport experience significantly associated with the rs1800496 polymorphism (p<0.05). In conclusion, genotype G/G could be inferred to be linked to the higher sport experience and athletic performance. Still, further studies with higher number of participants are needed to conclude the association of this polymorphism with athletic parameters.